2016
DOI: 10.1007/s00455-016-9762-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pharyngeal Swallow Effects of Recurrent Laryngeal Nerve Lesion on Bolus Shape and Airway Protection in an Infant Pig Model

Abstract: Recurrent laryngeal nerve (RLN) damage in infants leads to increased dysphagia and aspiration pneumonia. Recent work has shown that intra oral transport and swallow kinematics change following RLN lesion, suggesting potential changes in bolus formation prior to the swallow. In this study we used geometric morphometrics to understand the effect of bolus shape on penetration and aspiration in infants with and without RLN lesion. We hypothesized 1) that geometric bolus properties are related to airway protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 35 publications
4
39
0
Order By: Relevance
“…The results of this study show that similar patterns to what is found with bolus size also apply to swallowing mechanics and kinematics, namely movement of the posterior tongue and duration of epiglottal inversion. Our results agree with previous studies that documented that RLN and SLN lesion affected bolus size differently (13,19). Furthermore, how all these swallow parameters relate to airway protection deficits after lesion of either nerve also differs, indicating the specific mechanism of aspiration in SLN and RLN lesion is different.…”
Section: Despite Both Resulting In Increased Aspiration Rln and Sln supporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study show that similar patterns to what is found with bolus size also apply to swallowing mechanics and kinematics, namely movement of the posterior tongue and duration of epiglottal inversion. Our results agree with previous studies that documented that RLN and SLN lesion affected bolus size differently (13,19). Furthermore, how all these swallow parameters relate to airway protection deficits after lesion of either nerve also differs, indicating the specific mechanism of aspiration in SLN and RLN lesion is different.…”
Section: Despite Both Resulting In Increased Aspiration Rln and Sln supporting
confidence: 92%
“…Our own contradictory result around swallow duration likely resulted from using some different individuals in the analysis. Such variation was consistently found in all of the RLN lesion studies (14,19,23) as well as other studies of sensory disruption (25). Thus, in these animals, variation in response to insult seems to characterize dysphagia.…”
Section: Despite Both Resulting In Increased Aspiration Rln and Sln supporting
confidence: 55%
See 2 more Smart Citations
“…An infant pig model of RLN injury has provided novel insights concerning the role of the RLN and its neural connections in swallowing behavior. By using videofluoroscopic techniques, RLN injury has been shown to result in compromised airway protection and esophageal dysphagia (Gould et al, 2015), alterations in tongue shape (Gould, Yglesias, Ohlemacher, & German, 2017), and modified tongue and epiglottis kinematics during swallowing (Gould et al, 2016). However, these experiments were performed in neonatal and pre-weanling animals, better representing infants with immature nervous systems.…”
mentioning
confidence: 99%